Brief Notes: Simple Formula for Critical Tension of Truncated Structurally Orthotropic Shells of Revolution - Andrianov, I.V. (Engineering Transactions, 1993)
A structurally orthotropic shell of revolution is loaded by tensible forces applied to the ends of the shell. Stability of the structure is analyzed by means of the asymptotic method and the Galerkin procedure.